Desempenho do motor de um trator agrícola utilizando misturas diesel-biodiesel-etanol - Iacono, Giuseppe Eugênio Peruzo (2017)
The great challenge presented to the fuel market nowadays, is to find new energy alternatives, especially for diesel engines, since they represent almost the half of the national and international fleet, mostly transport means. Therefore, the aim of this research is evaluating the engine performance of an agricultural tractor used in ordinary field tasks, fueled with pure diesel A-S500, binary blends (diesel-biodiesel) and ternary blends (diesel-biodiesel-ethanol). The mechanical performance of the tractor was measured by an Eddy Current Dynamometer coupled to the tractor’s PTO, the gas emissions were measured by a combustion analyzer, and the high calorific value, measured by a calorimeter. The proposed diesel-biodiesel binary proportions (B7, B10, B15 and B20) were based on Law 13.263/2016 and the CNPE Resolution N.3/2015. These binary blends were evaluated without ethanol (E0) and in proportions of 1%, 3%, and 5% of anhydrous ethanol (99.6% purity). The dynamometric tests had four replicates, as calorific measurements were performed in triplicate and emission measurements were collected only once for each treatment. The results demonstrate that the calorific values decreased with the addition of ethanol and biodiesel. Power output remained stable with the addition of biodiesel, but decreased with the ethanol addition to all mixtures. In blends without ethanol, the power output increased with increasing biodiesel. Torque values decreased with the addition of ethanol to the mixtures. Compared to the B7E0 (commercial diesel), the decreases of Torque varied between 0.5% in B20E0 and 4.2% in B7E5 and B20E5. Brake specific consumption increased with the addition of biodiesel and ethanol, with slightly higher biodiesel influence in this increase. The thermal efficiency increased with the addition of ethanol, with emphasis on the B15E5 treatment that reached over 40% efficiency. The torque back up for six of the seventeen fuels stayed in the range considered regular, the other eleven had the performance on the range considered poor. The emission analysis showed that the amount of O2 in gas emissions decreased with the increase of the applied load. Reverse behavior occurred with CO2, which increased with increasing load. Biodiesel caused a small increase in NOx emissions in some blends, especially at high loads. On the other hand, ethanol caused a decrease of this gas in all treatments. It was verified that the addition of biodiesel and ethanol reduced CO emission at full load, with ethanol having a stronger effect. For low and medium loads, CO values were considered to be negligible. The temperature of the exhaust gases increased with increasing charge. However, the addition of oxygenated fuels had no effect on the temperature of the gases.